Diagnostic utility of antigen detection rapid diagnostic tests for Covid-19: a systematic review and meta-analysis - Somaye Ghasemi; Narges Nazari Harmooshi; Fakher Rahim (BMC, 2022)
Abstract Background The early detection of coronavirus disease (COVID-19) infection to improve disease management becomes the greatest challenge. Despite the high sensitivity of RT-PCR, not only it was reported that 20-67% of infected patients had false-negative results. Rapid diagnostic tests (RDTs) are widely used as a point-of-care test for SARS-CoV-2 detection in pharyngeal and blood specimens. It's more appealing since it's less time-consuming, doesn't seem to be as expensive, and doesn't need any specific training, but the poor sensitivity is the major limitation. Several reports indicated the rapid test of blood and pharyngeal samples has the same sensitivity as the RT-PCR, but some reports have lower sensitivity, especially in asymptomatic patients. Methods In the present survey, we investigate the eligible studies for the sensitivity and specificity of rapid tests and explore the factors that influence the result to help better diagnose COVID-19 infection. 20 studies met the inclusion criteria which imposed 33 different tests. Results Our findings showed the type of sample, the type of assay, the time of sampling, and the load of virus influence on the sensitivity of RDTs. Conclusion This research extends our knowledge of how to improve the sensitivity of RDTs to better diagnose the infected patients to address the controlling COVID-19 pandemic.